3 PKSS : forging directions for Korean studies in the Philippines - Lee, Aldrin P. ([Quezon City] : UP Department of Linguistics, 2014)
Includes bibliographical references
Keywords: Philippines Korean Studies Symposium; Korean language -- Philippines -- Congresses